(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2011)
With the advent of !’ewer nd mo em innovative chnologies in teaching commg up, it has become ally important for the teachers to shift their focus from dit/onal to modem method of teaching which is not /y student friendly but also aimed at practical penences and hands on tasks. The paper attempts o in an insight into the problems faced by teachers m faining and reinforcing the students in academic tasks d inclusion of the curriculum which best matches the responsibilities of the students which they are to take m the near future. The paper would demonstrate the ddel for effective and interesting teaching pedagogy ich is not only enriching but also creating among dents a thirst for and an appetite for learning by being olved in it. The research methodology would include scriptive design and analysis will be made on the sis of the response by the Faculty and students rsumg Higher Education. The model of great help for ovative teaching has also been proposed henceforth.